Statistics for Non-Statisticians - Madsen, Birger Stjernholm; Madsen, Stjernholm Birger (Berlin, Heidelberg Springer-Verlag Berlin Heidelberg, 2016)
This book was written for those who need to know how to collect, analyze and present data. It is meant to be a first course for practitioners, a book for private study or brush-up on statistics, and supplementary reading for general statistics classes. The book is untraditional, both with respect to the choice of topics and the presentation: Topics were determined by what is most useful for practical statistical work, and the presentation is as non-mathematical as possible. The book contains many examples using statistical functions in spreadsheets. In this second edition, new topics have been included e.g. within the area of statistical quality control, in order to make the book even more useful for practitioners working in industry.
Preface -- 1 Data Collection -- 2 Presentation of Data -- 3 Description of Data -- 4 The Normal Distribution -- 5 Analysis of Qualitative Data -- 6 Error Sources and Planning -- 7 Assessment of Relationship -- 8 Comparing Two Groups -- 9 Appendices -- Index.
includes bibliographical references and index
Catalography
Description based on publisher-supplied MARC data.
Keywords: Statistics; Statistics for Business, Management, Economics, Finance, Insurance; Statistical Theory and Methods; Statistics for Social Sciences, Humanities, Law